Selected sanitary systems in fire station buildings - Polarczyk, Iwona; Liebersbach, Joanna (Instal, 2025)
The article discusses the key technical and functional requirements for sanitary and hygiene systems in fire service buildings, with particular emphasis on the decontamination of firefighters, equipment, and vehicles. In response to the growing awareness of biological and chemical hazards, as well as applicable regulations, units of the State and Volunteer Fire Service in Poland are required to implement a division into clean and dirty zones. The paper analyses solutions for water supply and wastewater systems, as well as for dedicated facilities such as specialized laundries, vehicle wash stations, and washing areas for hoses and firefighting boots. Design requirements and essential equipment ensuring hygiene and safety within these zones are also described. The implementation of the proposed solutions is crucial for maintaining operational readiness, personnel health, and environmental protection. The article is additionally based on experience gained during the execution of real fire station projects, including facilities with rescue service units.
Keywords: sanitary systems; fire station; clean and dirty zones